2013
DOI: 10.1007/s00277-013-1775-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing DcR3 expression in relation to survivin and other prognostic factors in B cell non-Hodgkin’s lymphoma

Abstract: DcR3 expression was associated with other prognostic factors including survivin, reduced remission rates, and shorter event-free survival. Survivin is closely related to aggressive/highly aggressive subtypes of B cell NHL and is associated with shorter event-free survival. Both DcR3 and survivin expressions on bone marrow sections can be of help in diagnosing bone marrow infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…TGF-β1 was elevated before treatment in patient with DLBCL and dramatically decreased after treatment and correlated with advanced stages, high risk international prognostic index, bulky disease and partially or non-responded patients so it is linked to all bad prognostic factors, complete response was achieved in 42 patients (84.0%) while four patients (8.0%) had partial remission and four patients (8.0%) had no response to protocol of chemotherapy and these data were consistent with the study of Bedewy et al [20], in which 178 Egyptian patients (79.5%) achieved complete response after the R-CHOP regimen with follow-up period of 51 months.…”
Section: Tgf-β1supporting
confidence: 81%
“…TGF-β1 was elevated before treatment in patient with DLBCL and dramatically decreased after treatment and correlated with advanced stages, high risk international prognostic index, bulky disease and partially or non-responded patients so it is linked to all bad prognostic factors, complete response was achieved in 42 patients (84.0%) while four patients (8.0%) had partial remission and four patients (8.0%) had no response to protocol of chemotherapy and these data were consistent with the study of Bedewy et al [20], in which 178 Egyptian patients (79.5%) achieved complete response after the R-CHOP regimen with follow-up period of 51 months.…”
Section: Tgf-β1supporting
confidence: 81%
“…Some reports used a value greater than 5% as the survivin-positive cut-off, whereas others have used cut-offs of 10%, 25%, 30%, or 45% [17–19, 23, 24]. For localizing survivin immunostaining, some reports have used cytoplasmic survivin positivity, whereas others have used nuclear positivity, mixed-type positivity, or an immunoreactivity scoring system [17–19, 23, 24]. Thus, these previous studies have reported highly variable percentages of survivin-positive DLBCL in the range of 39.3% to 84.9% [19].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin expression in Ewing sarcoma, another type of human bone sarcoma, has been shown to be a poor prognostic marker . Survivin expression is a negative prognostic factor in both dogs with B‐cell lymphoma and in human B‐cell lymphoma . Survivin expression has been identified in select other canine neoplasms .…”
Section: Introductionmentioning
confidence: 99%